Improving MPGAA* for Extended Visibility Ranges - Hernández, Carlos; Baier, Jorge (Proceedings of the International Conference on Automated Planning and Scheduling, 2017)
Multipath Generalized Adaptive A* (MPGAA*) is an A*-based incremental search algorithm for dynamic terrain that can outperform D* for the (realistic) case of limited visibility ranges. A first contribution of this paper is a brief analysis studying why MPGAA* has poor performance for extended visibility ranges, which concludes that MPGAA* carries out an excessive number of heuristic updates. Our second contribution is a method to reduce the number of heuristic updates that preserves optimality. Finally, a third contribution is a variant of MPGAA*, MPGAA*-back, which we show outperforms MPGAA* and D* on a wide range of dynamic grid pathfinding scenarios, and visibility ranges.